2005
DOI: 10.1021/nl050623g
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Transport through a DNA Wire in a Dissipative Environment

Abstract: Electronic transport through DNA wires in the presence of a strong dissipative environment is investigated. We show that new bath-induced electronic states are formed within the bandgap. These states show up in the linear conductance spectrum as a temperature dependent background and lead to a crossover from tunneling to thermal activated behavior with increasing temperature. Depending on the strength of the electron-bath coupling, the conductance at the Fermi level can show a weak exponential or even an algeb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 28 publications
(69 reference statements)
0
71
2
1
Order By: Relevance
“…On the other hand, using a combination of molecular mechanics (for conformation ensemble generation) and quantum mechanics (for electronic structure calculation), Starikov et al [52] have shown that molecular motion and mismatches can actually increase the conductance under certain conditions and provide more coupled electronic states. In yet another work [53] , quantum-mechanical simulations on a simple DNA model in contact with a heat bath showed significant electronic structure modulation, which could be useful in describing observed Ohmic behaviour in short DNA wires using a tunnelling approach. More recently, a complete ab-initio study using the nonequilibrium Green's function approach, was carried out by Song, et al [54] , to study the effects of the correlated stretching/twisting of a (GC) dimer.…”
Section: Environmental Conditions and Molecular Conformationmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, using a combination of molecular mechanics (for conformation ensemble generation) and quantum mechanics (for electronic structure calculation), Starikov et al [52] have shown that molecular motion and mismatches can actually increase the conductance under certain conditions and provide more coupled electronic states. In yet another work [53] , quantum-mechanical simulations on a simple DNA model in contact with a heat bath showed significant electronic structure modulation, which could be useful in describing observed Ohmic behaviour in short DNA wires using a tunnelling approach. More recently, a complete ab-initio study using the nonequilibrium Green's function approach, was carried out by Song, et al [54] , to study the effects of the correlated stretching/twisting of a (GC) dimer.…”
Section: Environmental Conditions and Molecular Conformationmentioning
confidence: 95%
“…Usually, tight-binding Hamiltonians are employed to describe electronic structures of DNA duplexes -both explicitly (in the form of the "fishbone", "ladder" and similar models -see, for example, [51,53,58,60,[64][65][66][67][68][69][70][71][72] and the pertinent review articles [3,[73][74][75][76][77] ) and implicitly (within the framework of Marcus-type theories of charge transfer, for example, [55,[78][79][80][81] and the references therein). These works were successful in qualitatively (and sometimes even quantitatively) describing numerous experimental data (see, for example, [42,56,57,82,83] and the references therein) on transfer of injected single holes (or injected single electrons) through DNA duplexes.…”
Section: Critical Assessment Of the Biopolymer Charge Transfer/transpmentioning
confidence: 99%
“…Finally, transport in bio-molecules attracted more attention, in particular electrical conductance of DNA [286,287,288,289,290].…”
Section: Atomistic Transport Theorymentioning
confidence: 99%
“…For equilibrium problems, unitary transformations combined with variational approaches can be used, in non-equilibrium only recently some attempts were made to deal with the problem. [139] In this section we will consider the case of a multi-level electronic system in interaction with a bosonic bath [288,289]. We will use unitary transformation techniques to deal with the problem, but will only focus on the low-bias transport, so that strong non-equilibrium effects can be disregarded.…”
Section: 1 the Model Hamiltonianmentioning
confidence: 99%
“…We put forward new experimental setups to reveal the predicted effect and discuss possible applications of the DNA. In particular, we propose a design of the single molecule analog of the Esaki diode.Two approaches are widely used to describe the DNA: ab initio calculations [21][22][23][24][25][26][27][28] and model-based Hamiltonians [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The former can provide a detailed description but is currently limited to relatively short molecules (typically of the order of 10 base pairs long).…”
mentioning
confidence: 99%